Land Use in the Wildland-Urban Interface: Urban Sprawl and Smart Growth - Lauren McDonell; Martha C. Monroe; Gene Boles; Terri Mashour (EDIS, 2009)
Revised! FOR199, a 5-page illustrated fact sheet by Lauren McDonell, Martha C. Monroe, Gene Boles, and Terri Mashour, outlines the ecological, social, and economic effects of urban sprawl and describes the guiding principles of smart growth and how it can help address these issues. Includes references. Published by the UF School of Forest Resources and Conservation, July 2008.